Self-assembled micelles based on gambogenic acid-phospholipid complex for sustained-release drug delivery. (18th August 2019) - Wang, Beilei; Cheng, Weiye; Zhang, Caiyun; Bao, Youmei; Zha, Liqiong; Qian, Jiajia; Hong, Lufeng; Chen, Weidong
Abstract: Objective: To improve the water solubility and enhance the oral bioavailability of gambogenic acid (GNA). Methods: GNA-phospholipid complex (GNA-PLC) micelles were successfully prepared by anti-solvent method. Results: The encapsulation efficiency of GNA-PLC micelles can reach 99.33 % (w/w). The average particle size of the GNA-PLC micelles was 291.23 nm which was approximate agreed with the transmission electron microscopy (TEM). In vitro release profile showed the GNA-PLC and GNA-PLC micelles have significant sustained-release of GNA compared with crude GNA. Pharmacokinetic parameters indicated that the area under concentration–time curve (AUC0→t ) of GNA in cases of GNA-PLC and GNA-PLC micelles are 2.04- and 3.92-fold higher than crude GNA, respectively. Conclusions: The better water solubility and higher bioavailability of GNA in GNA-PLC micelles with significant sustained-release of GNA endow the nanoparticle with great potential in GNA delivery system.